2021
DOI: 10.3390/polym13040646
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Natural Fiber Reinforced Polymer Composite for Bullet Proof and Ballistic Applications

Abstract: Even though natural fiber reinforced polymer composites (NFRPCs) have been widely used in automotive and building industries, there is still a room to promote them to high-level structural applications such as primary structural component specifically for bullet proof and ballistic applications. The promising performance of Kevlar fabrics and aramid had widely implemented in numerous ballistic and bullet proof applications including for bullet proof helmets, vest, and other armor parts provides an acceptable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 275 publications
(147 citation statements)
references
References 151 publications
(256 reference statements)
1
144
0
2
Order By: Relevance
“…Studies on the processing effects and natural fibres properties show an improvement in mechanical properties parallel to the National Policy on Industry 4.0 (Industry 4WRD). Natural fibres have sparked great interest among researchers and industry players for their applications in the military [22], automotive [23][24][25][26][27], industrial [28][29][30][31][32][33], furniture [34], civil [35,36], and biomedical fields [37]. It is reported that the natural fibres global production exceeded 105 million metric tons in 2018 [38].…”
Section: Natural Fibrementioning
confidence: 99%
“…Studies on the processing effects and natural fibres properties show an improvement in mechanical properties parallel to the National Policy on Industry 4.0 (Industry 4WRD). Natural fibres have sparked great interest among researchers and industry players for their applications in the military [22], automotive [23][24][25][26][27], industrial [28][29][30][31][32][33], furniture [34], civil [35,36], and biomedical fields [37]. It is reported that the natural fibres global production exceeded 105 million metric tons in 2018 [38].…”
Section: Natural Fibrementioning
confidence: 99%
“…Polymeric composites are one of the most well-known materials that have lightweight properties and high durability for various functions [232][233][234][235][236][237][238][239]. Polymer composites exploit a wide range of applications due to their all-around excellent performance in mechanical, thermal, and electrical properties [240][241][242][243][244][245]. The inclusion of nanofillers inside polymer resins could provide promising properties for materials in almost every sector [246][247][248].…”
Section: Applications and Potential Use Of Carbon Nanotube-reinforced Polymer Compositesmentioning
confidence: 99%
“…Cellulose is an important structural component of the primary cell wall that surrounds the natural fibers, providing strength to plant cells, leaves, branches, and stems [78][79][80][81]. Cellulose is a semicrystalline polysaccharide consisting of units of d-glucopyranose interconnected by b-(1-4)-glucoside bonds [82][83][84][85]. However, in some cases when these natural fibers were used to reinforce hydrophobic matrices, a significant amount of hydroxyl groups in cellulose gave hydrophilic properties to natural fiber that resulted in very poor interface and resistance to moisture absorption [86].…”
Section: Region Where Resin Has Poorly Wetted the Fibermentioning
confidence: 99%